The bear ate your sandwich - Sarcone-Roach, Julia (New York : Alfred A. Knopf, 2015)
"When a sandwich goes missing, it seems that a bear is the unlikely culprit"--
Keywords: Bears -- Fiction; City and town life -- Fiction; Sandwiches -- Fiction; Dogs -- Fiction; Humorous stories; JUVENILE FICTION / Animals / Bears; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Lifestyles / City & Town Life